An Analysis of Expected Return and Risk for Determining the Efficient Portfolio of Financial Firms Listed on the Indonesia Stock Exchange - Pratama, Muhammad Isbar; Lismayani, Angri (Jurusan Matematika FMIPA UNM, 2025)
Investors can allocate their funds in many ways, but stock investment is one of the most popular. To obtain a favorable return and minimize risk, investors must consider several factors in order to achieve optimal investment outcomes. The formation of a stock portfolio serves as a means for investors to maximize their investment performance. The objective of this study is to calculate the expected return and portfolio risk to determine the efficient portfolio among financial companies listed on the Indonesia Stock Exchange. The calculations identify three portfolio combinations as the efficient ones. Portfolio 1, with a fund proportion of 40% : 60%, yields an expected return of 0.00032 or 0.032% and a portfolio risk of 0.059 or 5.9%. Portfolio 2 has an expected return of 0.0128 or 1.28% and a portfolio risk of 0.0504 or 5.04%. Portfolio 3 yields an expected return of 0.0057 or 0.57% and a portfolio risk of 0.0667 or 6.67%. Based on these results, Portfolio 2 is identified as the efficient portfolio, as it provides the highest expected return, albeit with relatively high risk. This type of investment is typically preferred by risk-seeking investors, who are inclined toward high-risk, high-return opportunities